2012
DOI: 10.5830/cvja-2012-041
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of D-dimer : fibrinogen ratio to diagnose pulmonary thromboembolism in patients admitted to intensive care units : cardiovascular topic

Abstract: IntroductionPulmonary thromboembolism (PTE) may increase D-dimer and decrease fibrinogen levels. However, in settings such as intensive care units (ICU) and in long-term hospitalised patients, several factors may influence D-dimer and fibrinogen concentrations and make them unreliable indicators for the diagnosis of PTE. The aim of this study was to evaluate the accuracy of D-dimer:fibrinogen ratio (DDFR) for the diagnosis of PTE in ICU patients.MethodsICU patients who were suspected of having a first PTE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…It can be used to diagnose or to rule out PE, but its specificity is very low in critically illness, since many clinical conditions associated with fibrin formation are present in ICU patients. 31 Even though only 23.2% of our patients had D-dimer quantification, D-dimer values were indeed significantly higher in those with PE.…”
Section: Discussionmentioning
confidence: 49%
“…It can be used to diagnose or to rule out PE, but its specificity is very low in critically illness, since many clinical conditions associated with fibrin formation are present in ICU patients. 31 Even though only 23.2% of our patients had D-dimer quantification, D-dimer values were indeed significantly higher in those with PE.…”
Section: Discussionmentioning
confidence: 49%
“…Wichmann et al reported autopsies revealing that 58% of patients had deep venous thrombosis, unsuspected before death, [28] meaning that new thromboembolism could not be recognized, if not critical. A D-dimer/fibrinogen ratio, calculated using the formula: (D-dimer [µg/ml] / fibrinogen [mg/dL]) × 100, has proven to be a specific marker for embolism, [26,27] and the ratio above 1.0 had 94% specificity in the diagnosis of pulmonary embolism in non-COVID-19 patients [26]. Indeed, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We constructed line graphs to visualize dynamic changes in fibrinogen and D-dimer levels in patients with COVID-19 and associated coagulopathy from each cluster. In addition, we graphically displayed sequential changes in D-dimer/fibrinogen ratio, a specific marker for embolism [26,27].…”
Section: Comparisons Of Covid-19 Subgroups Treated With Nafamostatmentioning
confidence: 99%
“…Plasma FIB is one of the most important factors in the coagulation cascade and its concentration can be elevated in other clinical conditions such as infections, haemodynamic impairment, cardiac, lung and aortic diseases and malignancies, as an acute-phase reactant [15]. The blood FIB concentration may increase in acute and chronic conditions as an acutephase reactant in canine ehrlichiosis.…”
Section: Discussionmentioning
confidence: 99%